Correlation between mental skills and anxiety during the covid-19 pandemic in university volleyball athletes - Muhamad Ilham; Nadya Dwi Oktafiranda; Rizka Antoni (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
The purpose of this study was to determine the relationship between mental skills and a person's level of anxiety during the Covid-19 pandemic. Mental skills as an important aspect in supporting achievement are very influential for athletes, especially when practicing and competing during the Covid-19 pandemic like today. Through this research, it will be seen how big the correlation is between the mental skills of an athlete and how much anxiety level is during the pandemic. The research method used in this research is associative quantitative method with a correlational approach. In this study, the samples were KOP volleyball athletes, State University of Jakarta. Data collection was preceded by distributing questionnaires to the athletes. The hypothesis testing technique carried out in this study used statistical analysis techniques of product moment correlation, followed by a t-test at a significant level of =0.50. The sample in this study was KOP Volleyball FIK UNJ athletes with 56 respondents, it can be concluded that there is a significant negative relationship between Mental Skills on Anxiety During the Covid-19 Pandemic with a correlation coefficient (rxy) of -0.459. That is, if the score of the mental skill variable increases, the score for the Anxiety variable During the Covid-19 Pandemic will decrease, but on the contrary if the Mental Skill score decreases, the Anxiety score During the Covid-19 Pandemic will increase.